Exploring the Distinctive Symbolic Interplay: Modern Vespa Piaggio User Community Dynamics in Makassar, Indonesia - Abidin, M. Zainul; Muhammad, Rahmat; Syam, Ridwan (Future Science, 2024)
Symbolic interaction is a form of reciprocal action carried out by two or more people to be able to translate and understand the symbols used in interaction. This includes interactions carried out by people who behave Fomo in a community. The research aims to find out the forms of Fomo behavior and understand the meaning of social action and symbolic interaction of members of the Makassar Move Community. The research used a qualitative approach with a case study strategy by determining informants using purposive informant selection. The results of this study found that Move Makassar members have a form of Fomo behavior by being so active in finding and sharing information about vespa matic and Move Makassar activities, always wanting to be involved in every activity, and excessive consumption of vespa matic accessories and modifications. The meaning of social action in the symbolic interaction of Move Makassar members is understood as an action that upholds the values of equality, togetherness and intimacy among them so that a sense of kinship arises.